(3GdYhdeI hYdGbJgG HGdgjefI GdJcfhdhLjIs - (3BOe egOj(B, (3GMeOs ((3GdbGgQI(B:s (3GdTQcI GdYGdejI ddWHGYI(B,s, 2001)
(3GdJLGQI GdOhdjI h efXeI GdJLGQI GdYGdejI h GdOhd GdfGejI h GdJLGQI GdNGQLjI ddOhd GdYQHjI eY JYQja GdYhdeI h JfGhd GdYhdeI ceaghe LOjO GdYhdeI h OjebQGWjI GdShb h GgejI OhQ GdYde h GdeYQaI h GdJWQb Gdi GdYhdeI h GdKbGaI h GdYhdeI h GdGef h SdHjGJ h GjLGHjGJ GdYhdeI ceG Je GdJWQb Gdi fbd GdJcfhdhLjG h GdeYQaI h OQGSI GdBdjGJ GdGbJUGOjI h GdbGfhfjI dfbd GdJcfhdhLjG h GNjQG GdTQcGJ GdeJYOOI GdLfSjGJ(B. s
(3eQGLY U(B.101s
Keywords: (3GdJLGQI GdNGQLjIs; (3GdJcfhdhLjGs; (3GdYhdeIs